IDENTIFYING ETHICAL DILEMMAS OF TOC/CHARTERED ACCOUNTANTS - Silva, Amélia (2014)
The way professionals deal with ethical dilemmas and the decisions they make may be guided by a personal and individual ideology, but these are also strongly influenced by their professional group and society. The focus in this paper is on situations as experienced by individuals in their day-to-day professional life. The data were collected with opened-end interviews. Respondents were asked to identify the ethical dilemmas they had been faced with during their professional life. Qualitative analysis shows that main dilemmas are about how to deal with “informal economy”, “false invoices” and “tax evasion”. This study aims to contribute to the discussion of ethical issues faced by TOC, thus promoting a large debate about the way TOC can help create a better society and consequently legitimating their existence as a professional organization of public interest.